Efektivitas Pijat Oksitosin terhadap Pengeluaran ASI pada Ibu Post Partum - anggraini dyah setiyarini; Nareswari Diska Nugraha (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Oxcytocin massage were solutions to help maximize the proplactin and oxytocin receptors so as to facilitate the process of maternal milk production.. This study aims to determine the effectiveness of the Oxcytocin massage in post partum mothers. Method: Pre- experimental research with one group pretest and posttest design approach. The population was all normal post partum mothers with the first child at Aura Syifa Kediri Hospital. A sample of 8 respondents with accidental sampling technique. Data collection used observation. Results: The results of data analysis used Wilcoxon test revealed that there was no effect of Oxcytocin massage. While the implementation of acupressure was known that there was an effect of acupressure therapy on milk production on. The results of data analysis used the mann whitney test was known that the value of Sig. 2- tailed (p value): 0.040 and alpha value (a): 0.05 so that the p value <a means that H0 was rejected and H1 was accepted. Conclusion: there are differences in the effectiveness of the Oxcytocin massage methods in increased milk production in Post Partum Mothers. Suggestion: The results of this study can be used as an alternative intervention in treating the physical and psychological needs of Postpartum Mothers. Nurses need to teach this technique to Postpartum Mothers to be more independent in dealing with milk production problems.